How the public nature of theology could address the proliferation of unaccredited theological qualifications in Africa - Banda, Collium (Stellenbosch Theological Journal, 2025)
The proliferation of questionable theological qualifications thrives on a privatised perception of theology that treats studying theology as a private matter between the believer and God. Unregistered theological institutions issuing ‘fake qualifications’ do so based on the perception that they are dealing with something private between God and them. This perception is undergirded by the belief that if God is pleased with their institutions, they do not need the approval of any human authority. This article argues that this privatised view of theology is challenged by the public nature of the Christian God, which means that any reflection on God should be done openly and be subject to public scrutiny. Therefore, this article calls African Pentecostals who are issuing fake qualifications and refusing to register with governing authorities, to recognise the public nature of theology, which means that theological institutions should meet public requirements for registrations. Equally, students that enrol in these unregistered institutions should be challenged to realise the public nature of theological education. This article therefore examines the public nature of theological education as a means of addressing the proliferation of questionable theological qualifications among African Pentecostal churches.